The role of transportation in the tourism activity in Lattakia region. - نعمان بتول; لميس ناصر (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Lattakia region is one of the most important tourist attractions in the Lattakia region, as it possesses tourism elements and services that are the basis for achieving human development, and the transport sector forms the cornerstone of the tourism service structure. Therefore, the development of the transport sector contributes to the establishment of tourism investments and the revitalization of their movement, hence the importance of The research dealing with the impact of the transportation sector on the reality of tourism activity in the Lattakia region Through this research, the elements of tourism attraction were studied, and the transportation sector was evaluated and its role in the distribution of tourist facilities. Transport problems were also highlighted, and the prospects for its development and its role in developing tourism activity were studied. The research concluded that tourism facilities such as hotels and restaurants are concentrated by 63% in the center The city of Lattakia, which is characterized by the presence of a network of high-quality roads, and developed scenarios such as coastal, environmental and natural tourism paths, by linking them to a network of modern roads, in addition to activating the role of rail and sea transport.